Immune cells transferred by colostrum do not influence the immune responses to foot-and-mouth disease primary vaccination - Bucafusco, Danilo; Pereyra, Walter Rodrigo; Mansilla, Florencia Celeste; Malacari, Darío Amilcar; Juncos, María S.; Di Giacomo, Sebastián; Ayude, Andrea Fabiana; Perez Filgueira, Daniel Mariano; Capozzo, Alejandra Victoria (Elsevier, 2019)
Little is known about the influence of maternal antibodies and immune cells transferred through colostrum on the immune responses of calves to the currently used foot-and-mouth disease (FMD) vaccines. Here we evaluated the humoral and cellular immune responses induced by vaccination of colostrum-deprived calves and calves that received equivalent amounts of colostrum preparations that differed in the presence or absence of maternal immune cells but contained the same quantity and quality of anti-foot-and-mouth disease virus (FMDV) antibodies. Three groups of 32-d-old calves (n = 3 per group) were deprived of colostrum and fed either whole immune colostrum or a cell-free colostrum preparation containing only anti-FMDV antibodies. All groups were immunized with 1 dose of an oil-adjuvanted commercial vaccine. Blood samples were collected periodically before vaccination and weekly after vaccination. Immune responses specific to FMDV were assessed based on T-cell proliferation, IFN-γ production, total and neutralizing serum antibodies, and isotype profile. All vaccinated calves developed IFN-γ and lymphoproliferative responses, irrespective of the colostrum received. Colostrum-deprived animals responded to vaccination with a primary IgM response followed by an increase of IgG1 titers. Conversely, antibody titers decreased in all colostrum-fed calves after vaccination. This study demonstrates for the first time that maternal immune cells transferred to the calves through colostrum do not modify immune responses to FMD vaccine, and it confirms the interference of maternal antibodies in the induction of humoral but not cell-mediated immune responses.